Ava Ranga Uka A Toroke Hau, Chile. Forschungen zur Landschaftsüberformung und kultischen Wassernutzung auf der Osterinsel. Die Arbeiten der Jahre 2012 und 2013 - Vogt, Burkhard (e-Forschungsberichte des DAI, 2023)
In 2008, the Commission for the Archaeology of Non-European Cultures (KAAK) initiated archaeological field studies in the small valley of Ava Ranga Uka A Toroke Hau in the centre of Easter Island. By studying several hydraulic structures, a small-sized, yet comprehensively anthropogenically changed cultural landscape could be investigated. The interdependence of the various hydraulic devices – attested to on the island for the first time and provisionally radiocarbon-dated from the mid-13th to the early 17th century – can, however, not be explained with utilitarian practice such as an agronomic use. The 2012 and 2013 field seasons have helped to develop contexts that suggest a special type of ritual function of the site as a water and fertility sanctuary.